Omega-3 Fatty Acids as Adjunctive Therapy in Periodontitis: A Scoping Review of Immune Modulation and Periodontal Tissue Regeneration - Wilma Adiwijaya; Yosua Kosen; Leonardo Jaya Setiadi T (Dentika: Dental Journal, 2026)
Periodontitis is a chronic inflammatory disease characterized by the progressive destruction of tooth-supporting tissues. It has also been reported to be associated with systemic conditions, such as diabetes mellitus and cardiovascular disease. Although scaling and root planing and other non-surgical periodontal therapies remain the mainstays of treatment, clinical outcomes may be limited by persistent inflammation and residual subgingival deposits. This has led to the exploration and investigation of adjuvant approaches. Omega-3 fatty acids, particularly eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), possess well-established anti-inflammatory and immunomodulatory properties. These compounds can enhance periodontal repair by modulating host immune responses and supporting tissue regeneration. As dietary supplements, the compounds are generally safe, affordable, and easily accessible. Therefore, this scoping review aims to map and synthesise evidence regarding the use of omega-3 fatty acids as adjunctive therapy in periodontitis, particularly in immune modulation and periodontal tissue regeneration. The study procedures were carried out in accordance with PRISMA-ScR guidelines Although clinical evidence remains limited, current studies suggest beneficial effects when omega-3 supplementation is combined with conventional periodontal therapy.   Keyword: Omega-3, adjunctive therapy for periodontitis, periodontal tissue regeneration